Transarterial chemoembolization with drug‐eluting beads is effective for the maintenance of the Milan‐in status in patients with a small hepatocellular carcinoma. Issue 10 (October 2015) - Manini, Matteo Angelo; Sangiovanni, Angelo; Martinetti, Laura; Viganò, Davide; La Mura, Vincenzo; Aghemo, Alessio; Iavarone, Massimo; Crespi, Silvia; Nicolini, Antonio; Colombo, Massimo
<x xml:space="preserve">Abstract</x> Transarterial chemoembolization (TACE) is the standard of care for the treatment of patients with an intermediate (Barcelona Clinic Liver Cancer [BCLC] B) hepatocellular carcinoma and to bridge patients with an early cancer to liver transplantation (LT). We explored the efficacy of TACE with drug‐eluting beads (DEB) in BCLC A patients. Included are all BCLC A patients unsuitable for resection or locoregional ablation who underwent a DEB TACE between 2006 and 2012. Treatment was carried out "a la demande" until complete tumor devascularization or progression beyond Milan criteria. In patients with a complete response (CR), a contrast computed tomography (CT) scan was repeated at 3‐month intervals during the first 2 years and then every 6 months alternating with abdominal ultrasound in the subsequent 3 years. Fifty‐five patients had 79 tumor nodules ranging 7 to 50 mm; 32 (58%) achieved a CR that was maintained up to 4 and 7 months in 21 (38%) and 17 (31%) patients, respectively. The 24‐ and 36‐month tumor‐free survivals were 21% and 9%, respectively. The overall cumulative progression beyond Milan criteria at 3, 6, 12, and 24 months was 2%, 5%, 30%, and 54%. LT eligibility was maintained for a median of 19 months (range, 2‐63 months). CR to first TACE was the strongest independent predictor of Milan‐in maintenance. In conclusion, DEB TACE may effectively bridge patients with an early cancer to LT, and a CR to the first procedure may guide patient prioritization during the waiting list. Liver Transpl 21:1259‐1269, 2015. © 2015 AASLD.